The effect of a family-based training program on the care burden of family caregivers of patients undergoing hemodialysis - Reza Sotoudeh; Saeid Pahlavanzadeh; Mousa Alavi (Wolters Kluwer Medknow Publications, 2019)
Background: The family caregivers of patients undergoing hemodialysis are faced with multiple physical, psychological, social, economic, and spiritual problems that increase their care burden. The present study was conducted to determine the effects of a family-based training program on the care burden of family caregivers of patients undergoing hemodialysis. Materials and Methods: The present controlled, randomized, clinical trial was conducted on 70 caregivers of patients undergoing hemodialysis in Ali Asghar and Zahray-e Marzieh hospitals in Isfahan, Iran, in 2017. After conducting convenient sampling, 70 participants were randomly assigned into 2 groups (35 in each group). The experimental group received the family-based training program and the control group received usual care plan. Data were collected using the Zarit Burden Scale before, immediately after, and 1 month after the intervention and were then analyzed by independent t-test, Chi-square, and Analysis of Covariance (ANCOVA) repeated measure. Results: The results showed that both groups were homogeneous in terms of their demographic data and showed no significant differences. The main effect of group was significant, indicating a significant decrease in care burden in the experimental group after the intervention (F1,67 = 1089, p < 0.001). However, the interaction of time and group was not significant, indicating insignificant difference in burden 1 month after intervention (p > 0.05). Conclusions: Since the family-based training program successfully reduced the burden of care immediately after intervention, similar family-based training programs are recommended to be designed and developed. However, insignificant time effect suggests further researches of long time effects of such program.